PENGARUH EFEKTIVITAS EDUKASI KESEHATAN TERHADAP PENGETAHUAN ORANG TUA TENTANG PENANGANAN PERTAMA PADA ANAK YANG TERSEDAK DI TK KENTEN PERMAI PALEMBANG - Oscar Ari Wiryansyah; wati, Nadia (Jurnal Kesehatan dan Pembangunan, 2024)
Choking is a condition where an object such as food or a foreign object enters the upper respiratory tract which causes difficulty breathing. Children aged 0-6 years often experience cases of choking. Children often choke on food and foreign objects, 59.5% of children choke on food, 31.4% of children choke on foreign objects and 9.1% do not know what causes children choke. The purpose of this study was to identify parents' knowledge about first aid for choking children. This research method uses analytic survey research, namely quantitative research which explains the influence of health education on the level of parental knowledge about the first handling of choking in children. Sampling used a accidental sampling technique, with a sample size of 49 parents of students in Kindergarten Kenten Permai Palembang. 3. There is an influence of health education on the level of mother's knowledge about handling a choking child in Kindergarten Kenten Permai Palembang